2021
DOI: 10.1088/1478-3975/abcb66
|View full text |Cite
|
Sign up to set email alerts
|

Potential SARS-CoV-2 protease Mpro inhibitors: repurposing FDA-approved drugs

Abstract: Using as a template the crystal structure of the SARS-CoV-2 main protease, we developed a pharmacophore model of functional centers of the protease inhibitor-binding pocket. With this model, we conducted data mining of the conformational database of FDA-approved drugs. This search brought 64 compounds that can be potential inhibitors of the SARS-CoV-2 protease. The conformations of these compounds undergone 3D fingerprint similarity clusterization. Then we conducted docking of possible conformers of these drug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…128,129 In addition to docking, other computational methods have been used to identify new SARS-CoV-2 M-pro inhibitors. These methods include pharmacophores 76,130,131 ; combined quantum mechanics/molecular mechanics (QM/MM) methods 132,133 ; a Docking Consensus Approach and Common Hits Approach that combine molecular dynamics simulations with molecular docking and pharmacophores, respectively 131 ; interactive molecular dynamics simulation in virtual reality 134 ; Quantitative Structure-activity Relationship models, 115 and binding free energies calculations. 82,116,135 Among the various methods to calculate protein-ligand binding affinities, Free Energy Perturbation (FEP) has been used successfully to predict new M-pro inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…128,129 In addition to docking, other computational methods have been used to identify new SARS-CoV-2 M-pro inhibitors. These methods include pharmacophores 76,130,131 ; combined quantum mechanics/molecular mechanics (QM/MM) methods 132,133 ; a Docking Consensus Approach and Common Hits Approach that combine molecular dynamics simulations with molecular docking and pharmacophores, respectively 131 ; interactive molecular dynamics simulation in virtual reality 134 ; Quantitative Structure-activity Relationship models, 115 and binding free energies calculations. 82,116,135 Among the various methods to calculate protein-ligand binding affinities, Free Energy Perturbation (FEP) has been used successfully to predict new M-pro inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…This includes Wilms tumor, rhabdomyosarcoma, Ewing’s sarcoma, trophoblastic neoplasm, testicular cancer, and certain types of ovarian cancer . mithramycin and dihydroergotamine have been also computationally studied by other groups in the search of antivirals against SARS-CoV-2, ,, but none of them has been tested in vitro or in vivo. ,, Mithramycin is an antibiotic that inhibits the synthesis of the bacterial RNA () and is not currently on the market because it is not approved for cancer therapy. Dihydroergotamine is a widely used antimigraine drug approved in 1946, still on the market also as a nasal spray formulation (ideal for the intended use against respiratory disease) with well-known record of dosage and side effects on patients.…”
Section: Resultsmentioning
confidence: 99%
“…36 mithramycin and dihydroergotamine have been also computationally studied by other groups in the search of antivirals against SARS-CoV-2, 18,24,25 but none of them has been tested in vitro or in vivo. 19,25,26 Mithramycin is an antibiotic that inhibits the synthesis of the bacterial RNA (https://www. fermentek.com/product/mithramycin-plicamycin) and is not currently on the market because it is not approved for cancer therapy.…”
Section: Identification Of Fda-approved Mithramycin Andmentioning
confidence: 99%
“…Cynarine, eravacycline, and prexasertib represented outstanding inhibitory activity with IC 50 values of 1.82 μ M, 1.65 μM, and 1.99 μM, respectively. Interestingly, eravacycline was also identified in recent virtual screens of FDA-approved drugs for repurposing as COVID-19 treatments [ 14 , 15 ]. The docking modes of cynarine, eravacycline, and prexasertib indicated that between the two catalytic dyad residues His41 and Cys145, Cys145 was involved in binding with all three chemicals ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%